Composition and Functional Characterization of Microbiome Associated with Mucus of the Coral Fungia echinata Collected from Andaman Sea - Badhai, Jhasketan; Ghosh, Tarini S.; Das, Subrata K. (Frontiers in Microbiology, 2016)
This study describes the microbial community composition and functions of the microbiome associated with the mucus of the coral Fungia echinata based on metagenomic approach. Metagenome sequence data showed a dominance of the class Gammaproteobacteria followed by Alphaproteobacteria, Betaproteobacteria, Deltaproteobacteria, Flavobacteriia, Bacilli and Clostridia. At the order level the most abundant groups were Pseudomonadales, Oceanospirillales, Alteromonadales and Rhodobacterales. The genus Psychrobacter was the most predominant followed by Thalassolituus and Cobetia, although other genera were also present, such as Sulfitobacter, Pseudoalteromonas, Oleispira, Halomonas, Oceanobacter, Acinetobacter, Pseudomonas, Vibrio, and Marinobacter. The metabolic profile of the bacterial community displayed high prevalence of genes associated with core-housekeeping processes such as carbohydrates, amino acids, proteins, and nucleic acid metabolism. Further, high abundance of genes coding for DNA replication and repair, stress response, and virulence factors in the metagenome suggested acquisition of specific environmental adaptation by the microbiota. Comparative analysis with other coral metagenome exhibits marked differences at the taxonomical and functional level. This study suggests the bacterial community compositions are influenced by the specific coral micro-niche and the oligotrophic marine environment.